2021
DOI: 10.36740/wlek202109101
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Infections in Ukraine: Results of a Multicenter Study

Abstract: The aim: To obtain the estimates of the сurrent incidence rate of perinatal infections, risk factors, as well as their associated impact on mortality and determine the antimicrobial resistance of responsible pathogens in Ukraine. Materials and methods: We performed a multicentre retrospective cohort study was based on surveillance data. This study included infants aged 0 to 6 days delivered in 2017-2019 at 11 Ukrainian regional perinatal centers. Definitions of perinatal infections and mortality were used from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…One study reported that the most common agents for perinatal infections in newborn infants born in 2017–2019 in Ukraine were: Escherichia coli , Streptococcus agalactiae , Staphylococcus aureus , Klebsiella pneumoniae , Coagulase ‐ negative staphylococci , Enterobacter and Pseudomonas aeruginosa 99 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that the most common agents for perinatal infections in newborn infants born in 2017–2019 in Ukraine were: Escherichia coli , Streptococcus agalactiae , Staphylococcus aureus , Klebsiella pneumoniae , Coagulase ‐ negative staphylococci , Enterobacter and Pseudomonas aeruginosa 99 …”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…The design was observational in 330 studies (94%) and interventional in 20 (6%) studies, with 12 to 22 831 (median [IQR], 115 [61-270]) episodes per study, and the inclusion period’s length varying from 3 months to 36 years (median [IQR], 5 [2-10] years). Studies included neonates (59 studies [16%]; 6549 episodes [4%]), children (101 studies [27%]; 21 511 episodes [14%]), adults (64 studies [17%]; 15 362 episodes [10%]), neonates and children (68 studies [18%]; 26 992 episodes [17%]),…”
Section: Resultsmentioning
confidence: 99%
“…This is related to the speci city of drug use during pregnancy, and β-lactam antibiotics are relatively safe to use during pregnancy [6]. Optimizing the management and empiric antimicrobial therapy can reduce infections in pregnant women, such as the more common urinary tract infections, so prevention is still a key factor [7]. Although antimicrobial therapy may reduce preterm birth and low birth weight, consistent with the role of infection in adverse pregnancy outcomes, there is limited con dence in the effects given the uncertainty of the evidence.…”
Section: Discussionmentioning
confidence: 99%